2019
DOI: 10.1634/theoncologist.2019-0627
|View full text |Cite
|
Sign up to set email alerts
|

FDA Approval Summary: Ruxolitinib for Treatment of Steroid-Refractory Acute Graft-Versus-Host Disease

Abstract: On May 24, 2019, the Food and Drug Administration approved ruxolitinib for steroid-refractory acute graft-versus-host disease (SR-aGVHD) in adult and pediatric patients 12 years and older. Approval was based on Study INCB 18424-271 (REACH-1; NCT02953678), an open-label, single-arm, multicenter trial that included 49 patients with grades 2-4 SR-aGVHD occurring after allogeneic hematopoietic stem cell transplantation. Ruxolitinib was administered at 5 mg twice daily, with dose increases to 10 mg twice daily perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 31 publications
0
68
1
1
Order By: Relevance
“…A response rate of 81% in aGVHD was achieved in this study leading to promises. In May 2019, the Food and Drug administration approved ruxolitinib for steroid‐refractory aGVHD in adult and pediatric patients 12 years older based on REACH‐1 (NCT02953678) study, which showed a day‐28 overall response rate (primary endpoint) of 57.1% (95% CI, 42.2‐71.2) 13 …”
Section: Introductionmentioning
confidence: 99%
“…A response rate of 81% in aGVHD was achieved in this study leading to promises. In May 2019, the Food and Drug administration approved ruxolitinib for steroid‐refractory aGVHD in adult and pediatric patients 12 years older based on REACH‐1 (NCT02953678) study, which showed a day‐28 overall response rate (primary endpoint) of 57.1% (95% CI, 42.2‐71.2) 13 …”
Section: Introductionmentioning
confidence: 99%
“…The FDA-adjudicated ORR at day 28 (excluding patients who had received any other systemic therapy, n=49) was similar to the full population at 57.1% (95% CI 42.2-71.2%). 58 Six-month OS in day-28 responders (n=39) was 73.2% (95% CI 55.9-84.6%) compared with other responders (n=13) at 35.9% (95% CI 11.7-61.3%) and nonresponders (n=19) at 15.8% (95% CI 3.9-34.9%). At day 28, among patients with any response on combination therapy (n=43), 55.8% (n=24) reduced their steroid dose by ≥ 50% such that the median corticosteroid dose was 156.3 mg/day on day 1 reduced to a median of 62.5 mg/day by day 28.…”
Section: Treatmentmentioning
confidence: 89%
“…57 Steroid-Refractory Acute GVHD Despite aggressive steroid treatment, response rates are poor, hovering around 40%, and most patients require second-line therapy. 16,58 Indications for an additional agent include GVHD progression after 3 days of steroids, persistent grade III GVHD not improving after 7 days of steroid, persistent grade GVHD not improving after 14 days of steroid, or inability to tolerate steroid taper. 16 Until recently, there was no standard treatment for steroid-refractory disease.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, pSTAT3-inhibited iTregs preserve donor antileukemia activity necessary for the beneficial graft-versus-leukemia effect. Despite recent FDA approvals for agents to treat steroid refractory acute (60) and chronic GVHD (61), advances in GVHD prevention are needed. Additionally, innovative approaches are needed in solid-organ allotransplantation to reduce dependence on broadly suppressive calcineurin inhibitors and glucocorticoids.…”
Section: Figure 8 Human Pstat3-inhibited Itregs Maintain Antileukemimentioning
confidence: 99%